One more thing [compact disc, unabridged] : stories and other stories - Novak, B. J., 1979- (Random House Audio, 2014)
A boy wins a $100,000 prize in a box of Frosted Flakes, only to discover that claiming the winnings may unravel his family. A woman sets out to seduce motivational speaker Tony Robbins. A school principal unveils a bold plan to permanently abolish arithmetic. An acclaimed ambulance driver seeks the courage to become a singer-songwriter. Author John Grisham contemplates a monumental typo. These and many more short stories are included in an original debut collection.